Заборона суміщення функції судового розгляду і інших процесуальних функцій як підстава самовідводу, відводу - Дем’янчук, В.; Demianchuk, V.; Денісова, Г.; Denysova, G. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Традиційним в нашому законодавстві є розмежування функції вирішення справи від інших процесуальних функцій і це порушення згідно п. 2 ч. 2 ст. 412 КПК України є безумовною підставою для скасування вироку, ухвали. Недопущення змішування функцій учасників кримінально-процесуальної діяльності – важлива гарантія прав сторін в процесі і для цього існує інститут відводів. На наш погляд, це може бути пояснено і з точки зору психології, адже суміщення в одній особі функції правосуддя та будь-якої іншої функції чи ролі суперечить її законам. Автори вважають за необхідне передбачити такий спосіб забезпечення засади змагальності, який би заборонив виконувати одному учаснику кримінального процесу дві або більше функції у одному кримінальному провадженні. Самовідвід чи відвід судді слід застосовувати і до тих ситуацій, коли він виконував в даному провадженні інші процесуальні функції як до, так і після обрання (призначення) на посаду судді.The article deals with legislature regulations aimed at differentiation of the functions in legal proceedings and violation of them. Traditional approach in our legislature is separation of the functions in court hearings and other procedural functions. The violation of it is the basis for verdict being revoked. Debarment of combining functions performed by the participants in the trial is an important guarantee of the parties’ rights in legal proceedings. The institute of disqualification in court and self- dismissal of the participant in trial is the guard post of it. From the point of view of psychology combining in one person functions of justice and any other function contradicts the very nature of human. The authors consider that legislature should ensure the principles of fair competition of the parties in trial, introduce the regulations which would prohibit any participant in the court hearings to combine two or more functions in one criminal proceeding. The article suggests to amend Article 22 in part 3 of Criminal Procedural Code of Ukraine with the following: «Participant in the trial can not combine two or more functions in one criminal proceeding». The procedure of disqualification in court and self- dismissal of the participant in trial can also be applied in situations when a judge performs the function of witness to the accident, expert, specialist, interpreter, investigator, prosecutor, advocate (both before and after appointment to the post).
Prohibition of Amalgamation of Trial’s Function and Other Procedural Functions as a Basis for Self-rejection, Rejection.
Keywords: суддя; потерпілий; цивільний позивач; цивільний відповідач; представник; самовідвід; відвід; judge; victim; civil plaintiff; civil defendant; representative; self-rejection; rejection